Determination of Heavy Metals in Alpinia oxyphylla Miq. Collected from Different Cultivation Regions - Dan Zhou; Yurong Fu; Weiyong Lai; Junqing Zhang (Journal of Analytical Methods in Chemistry)
20 batches of Alpinia oxyphylla Miq. were collected from Yunnan, Guangdong, Guangxi, and Hainan province in China. The contents of heavy metals of As, Hg, Pb, Cd, and Cu were determined and compared. The results indicated that geographical source might be a major factor to influence the contents of heavy metals of arsenic (As), mercury (Hg), lead (Pb), cadmium (Cd), and copper (Cu) in Alpinia oxyphylla Miq. Compared to the criteria of heavy metals, the contents of As, Hg, Pb, and Cd in almost all the samples were in accordance with The Green Trade Standards. The contents of Cu were higher than the criteria for heavy metals except the samples from Changxing town, Qiongzhong county, Maoyang town, Qiongzhong county, Wupo town, Tunchang county, and Nanlv town, Tunchang county, in Hainan province. The best cultivation regions of Alpinia oxyphylla Miq. were from Changxing town, Qiongzhong county, Maoyang town, Qiongzhong county, Wupo town, Tunchang county, and Nanlv town, Tunchang county, in Hainan province. This research would provide the scientific basis for quality control and standardization of Alpinia oxyphylla Miq.